On the Reduction of the Linear System of the Differential Equations with coefficients of oscillating type to the Triangular Kind in the Non-resonant Case - S.A. Shchogolev (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
For the linear homogeneous differential system, whose coefficients are represented as an absolutely and uniformly convergent Fourier-series with slowly varying coefficients and frequency, the conditions of the existence of the transformation which leads it to triangular kind, are obtained in the non-resonant cases.